Evans–Showell-type polyoxometalate-based metal–organic complexes with novel 3D structures constructed from flexible bis-pyrazine–bis-amide ligands and copper metals: syntheses, structures, and fluorescence and catalytic properties. Issue 6 (23rd January 2019) - Li, Feng-Cai; Li, Xi-Li; Tan, Li-Kun; Wang, Jin-Tang; Yao, Wei-Zhong
Abstract : Two 3D Evans–Showell-type POM-based copper–bis-pyrazine–bis-amide complexes show good heterogeneous catalytic activity for the oxidation of benzyl alcohol. Abstract : Two new Evans–Showell-type polyoxometalate (POM)-based metal–organic complexes, namely Cu3 (L1 )1.5 (H2 O)5 [Co2 Mo10 H4 O38 ]·5H2 O (1 ), [Cu(L2 )0.5 (H2 O)2 ]2 [Co2 Mo10 H4 O38 ]·6H2 O (2 ) (L1 = N, N ′-bis(2-pyrazinecarboxamide)-1, 4-butane, L2 = N, N ′-bis(2-pyrazinecarboxamide)-1, 6-hexane), were successfully synthesized and structurally characterized by single-crystal X-ray diffraction, elemental analysis, IR spectroscopy, powder X-ray diffraction (PXRD) and thermogravimetric analyses (TGA). In complex1, the adjacent [Co2 Mo10 H4 O38 ] 6− polyoxoanions are linked by Cu II ions to form a 1D Cu–[Co2 Mo10 H4 O38 ] 6− inorganic chain, which is further linked by ligandL1 and [Co2 Mo10 H4 O38 ] 6− polyoxoanions, forming a 3D metal–organic framework. In complex2, the adjacent [Co2 Mo10 H4 O38 ] 6− polyoxoanions link the Cu II ions to generate a 2D Cu–[Co2 Mo10 H4 O38 ] 6− inorganic layer, which is further connected with bidentate ligandsL2 to obtain a 3D metal–organic framework. The structural diversities of compounds1 and2 showed that the spacer lengths of the flexible bis-pyrazine–bis-amide ligands play important roles in tuning the structures of the title complexes. Compounds1 and2 represent the first examples of 3D frameworks based on the Evans–Showell-type polyoxoanions and Cu-bis-pyrazine–bis-amide coordination complexes. Moreover, the ligandL1 was first successfully introduced into the POM system. The electrochemical and fluorescence properties of compounds1 and2 were discussed. As heterogeneous catalysts, compounds1 and2 have good catalytic activity for the oxidation of benzyl alcohol. Moreover, compound2 has higher catalytic performance with 100% conversion and 98.0% selectivity for benzoic acid at 10 h. The difference in their catalytic performance may be mainly due to the difference of their structures. The catalysts can be recovered and reused without displaying any significant loss of activity.